2022
DOI: 10.3389/fpsyt.2022.951376
|View full text |Cite
|
Sign up to set email alerts
|

The Ketogenic Diet for Refractory Mental Illness: A Retrospective Analysis of 31 Inpatients

Abstract: Background and HypothesisThe robust evidence base supporting the therapeutic benefit of ketogenic diets in epilepsy and other neurological conditions suggests this same metabolic approach may also benefit psychiatric conditions.Study DesignIn this retrospective analysis of clinical care, 31 adults with severe, persistent mental illness (major depressive disorder, bipolar disorder, and schizoaffective disorder) whose symptoms were poorly controlled despite intensive psychiatric management were admitted to a psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…When MPC1 is deficient, it may cause neurological diseases such as epilepsy. High-fat and low-carbohydrate diet can reduce the ratio of NADH/NAD+, promote the production of cytoplasmic aspartate in the cytoplasmic part of MAS, and provide fatty acids and ketone bodies as alternative substrates to replace TCA cycle to bypass the above defects, so as to achieve the role of auxiliary treatment of mitochondrial diseases and protection of nerves [16].…”
Section: Improve Mitochondrial Functionmentioning
confidence: 99%
“…When MPC1 is deficient, it may cause neurological diseases such as epilepsy. High-fat and low-carbohydrate diet can reduce the ratio of NADH/NAD+, promote the production of cytoplasmic aspartate in the cytoplasmic part of MAS, and provide fatty acids and ketone bodies as alternative substrates to replace TCA cycle to bypass the above defects, so as to achieve the role of auxiliary treatment of mitochondrial diseases and protection of nerves [16].…”
Section: Improve Mitochondrial Functionmentioning
confidence: 99%
“…Modest dietary changes can be more effective in the treatment of metabolic syndrome than commonly used antidiabetic drugs in improving CVD risk [163]. Specifically, improvement in the cluster of components of metabolic syndrome is intimately connected with carbohydrate restriction in adults [164–167,168 ▪ ,169 ▪ ,170 ▪ ,171,172 ▪▪ ,173–177,178 ▪▪ ,179–180,181 ▪ ] and in adolescents [182]. LCDs have been shown to improve other CVD risk factors, as well, such as visceral fat, blood pressure, Lp(a) and inflammation [183–189].…”
Section: Effects Of Low Carbohydrate Diets On Cardiovascular Disease ...mentioning
confidence: 99%
“…LCDs have been shown to improve other CVD risk factors, as well, such as visceral fat, blood pressure, Lp(a) and inflammation [183–189]. It is therefore highly relevant that LCDs have been studied in numerous RCTs and case reports which show improvement in glucose, lipid and insulin-based CVD risk factors, including an LCD-mediated reduction in the need for hypoglycemic medication [178 ▪▪ ,190,191 ▪ ,192,193 ▪ ,194 ▪ ,195,196 ▪ ,197,198 ▪▪ ,199 ▪ ].…”
Section: Effects Of Low Carbohydrate Diets On Cardiovascular Disease ...mentioning
confidence: 99%
“…1, 2 Preliminary data from case reports and retrospective analyses have suggested that a ketogenic diet may also have beneficial effects in bipolar disorder. 3, 4, 5…”
Section: Introductionmentioning
confidence: 99%